Greek Women’s Habits through the Eyes of Early Travellers to Chios - Mitsi, Efterpi (Historein, 2022)
Focusing on the images and interpretation of clothing in relation to geographical and cultural space, this article explores the verbal and visual representation of the women of Chios in sixteenth- and seventeenth-century travel writing. The juxtaposition of text and image epitomises the women’s ambiguous depiction in relation to the growing interest in cultural differences as they are manifested through customs of dress. In Nicolas de Nicolay’s Navigations, the beauty of the women, who are compared to goddesses and nymphs, parallels the island’s wealth, fertility and glorious past. At the same time, the idealisation evident through the allusions to antiquity is counterbalanced by the women’s sexuality and extravagance, revealed through their dress, gesture and customs. In the context of the Ottoman Empire, which was seen by Nicolay and other early travellers as a realm of sexual depravation, the proliferation and reproduction of the images of Chian women suggest the ways in which gender, in particular, the dressed female body, is used to construct regional, national, and confessional identities. To view the full text, click on the button "HTML".